A discursive–institutional perspective on transformative governance: A case from a fire management policy sector. (13th June 2018) - Bosomworth, Karyn
Abstract: Scholarship around questions of climate change adaptation is increasingly concerned with ideas of transformative adaptation and its governance through critical re‐evaluation of beliefs, values and associated institutions. For public policy sectors, the concept of transformative governance brings attention to their capacities for supporting and engaging in such governance. While much adaptation research and practice informs technical and structural understandings of these capacities (e.g., governance arrangements, learning systems and adaptation planning), most of this research (and practice) has ignored less formal, yet equally important dimensions of public administration and governance. Institutional scholarship highlights that dominant norms, beliefs, and philosophical ideas underpin how policy sectors structure their policy responses and engagement in governance. Discursive Institutionalism suggests that examining a sector's dominant discourse can provide insights into these "institutional logics". This paper therefore argues that understanding a policy sector's institutional logics is a crucial part of working toward enabling transformative governance of adaptation. This argument is developed through a case study of the institutional logics operating in the fire management policy sector of Victoria, Australia, and the potential influence of these logics on that sector's capacities to engage in transformative governance. Findings suggest this sector's institutional logics may currently constrain its capacities to engage in transformative governance and highlight the need for greater attention to socioinstitutional dimensions of public administration to help catalyze transformative governance of (and for) adaptation.